Isolation and characterization of hydrocarbon-utilizing bacteria from soils contaminated with used engine oil and diesel oil - Ridzuan Kamarudin, Mohamad; Marlizan, Shafiza; Md Anis, Nuraizah; Feisal Merican, Amir (Malaysian Journal of Science, 2001)
Bacteria were isolated from a train workshop in Sentul, Kuala Lumpur (S-I), a car and motorcycle workshop in Kampong Kerinci, Kuala Lumpur (S-II), and a boat workshop in Port Dickson, Negri Sembilan (S-III). All the microorganisms were isolated using Liquid Culture Enrichment Method with dilution streaking method and dilution spreading method. A total of 93 bacteria and 1 strain of yeast were isolated from S-I, 76 bacteria were isolated from S-ll and 147 bacteria were isolated from S-lll. Further identification using a commercially made identification kit revealed that rnost isolates are from the genus Pseudomonas, Acinetobacter and Aeromonos.